Land Use Response in Volume of Infiltrated Analysis to Control Fire Risk in the Liang Anggang Tropical Peatland Forest in South Kalimantan - Novitasari; Nurfansyah; Kurdi, Holdani; Ramadhani, Muhammad Aulia; Maulana, Muhammad; Nailia, Nur (Civil and Environmental Science Journal (CIVENSE), 2024)
Liang Anggang Protected Forest is an area formed from peatland. Peatlands have a role in conserving water resources, reducing floods, preventing seepage of seawater, and so on. Damage to the water system in peatlands is often caused by individual activities that are not well controlled. This is thought to have resulted in the depletion of water in the peat soil, making the soil dry and flammable in the dry season. This research aims to analyze the rate of infiltrated water in the Liang Anggang Block 1 Protected Forest area. It was also found that the volume of infiltrated water in the natural conditions of the protected forest, assuming that there is no current use of the protected forest area, is 9,097,126.998 m3/year, and the total after there is current utilization of 8,498,889.127 m3/year. Due to the current utilization carried out in the area under review, the infiltration volume value decreased by 6.576%. Based on this research, it is very necessary to maintain land use in the Liang Anggang protected forest to maintain the volume of infiltrated water in the area.